VALUE ADDED TAX ON DONATION-BASED FINTECH CROWDFUNDING - Ni Putu Anik Suardani; Suparna Wijaya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Uptrend's use of donation-based crowdfunding to raise funds digitally from year to year has not been matched by discussions from the Value Added Tax (VAT) point of view in Indonesia. This study aims to explore the business process of kitabisa.com as one of the providers of donation-based crowdfunding services in Indonesia and review its VAT imposition scheme. The research was conducted using qualitative methods through interview and documentation techniques of data collection. The results of the research show that kitabisa.com acts as an intermediary that provides platform services for online fundraising within a certain period and earns returns by deducting 5% of each fundraising collected. The delivery of the platform provides services in the donation-based crowdfunding scheme as carried out by kitabisa.com fulfills the provision of the delivery of taxable services in Article 4 paragraph (1) letter c of the VAT Law and has the potential to be established as a taxable entrepreneur so that it is obliged to collect VAT on the delivery of the platform provides services it performs.